Importance of electron distribution profiles to chorus wave driven evolution of Jovian radiation belt electrons - Jing Huang; XuDong Gu; BinBin Ni; Qiong Luo; Song Fu; Zheng Xiang; WenXun Zhang (Earth and Planetary Physics, 2018)
Wave-particle interactions triggered by whistler-mode chorus waves are an important contributor to the Jovian radiation belt electron dynamics. While the sensitivity of chorus-driven electron scattering to the ambient magnetospheric and wave parameters has been investigated, there is rather limited understanding regarding the extent to which the dynamic evolution of Jovian radiation belt electrons, under the impact of chorus wave scattering, depends on the electron distribution profiles. We adopt a group of reasonable initial conditions based upon the available observations and models for quantitative analyses. We find that inclusion of pitch angle variation in initial conditions can result in increased electron losses at lower pitch angles and substantially modify the pitch angle evolution profiles of > ~500 keV electrons, while variations of electron energy spectrum tend to modify the evolution primarily of 1 MeV and 5 MeV electrons. Our results explicitly demonstrate the importance to the radiation belt electron dynamics in the Jovian magnetosphere of the initial shape of the electron phase space density, and indicate the extent to which variations in electron energy spectrum and pitch angle distribution can contribute to the evolution of Jovian radiation belt electrons caused by chorus wave scattering.